PENGARUH VARIAN MENU DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA RUMAH MAKAN PAK QOMAR SIDAYU GRESIK - Siswanto, Siswanto; Widodo, Muji (Universitas Nusa Cendana, 2024)
This study aims to examine the effect of menu variant and service quality on purchasing decision at Pak Qomar restaurant Sidayu Gresik. The population in this study were customers to Pak Qomar restaurant Sidayu Gresik for 4 months. How to determine the sample using Slovin's theory as many as 99 respondents which in this study were fulfilled into 100 respondents. The data analysis used is the IBM SPSS 22 program. This study uses a quantitative approach with multiple regression analysis method. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple regression. The results showed that there was a partial and simultaneous influence of menu variant and service quality on purchasing decision at Pak Qomar restaurant Sidayu Gresik